Morphometric parameters of black currant berries and racemes under the conditions of Northwest Russia - O. A. Tikhonova (Труды по прикладной ботанике, генетике и селекции)
Background. It is important to study morphometric parameters of productivity in cultivars because it allows us to identify the most productive cultivars and valuable genotypes with improved characteristics of the mechanical composition of berries for use in breeding practice.Materials and methods. Morphometric parameters of berries and racemes were assessed at Pushkin and Pavlovsk Laboratories of VIR in 2016–2018. Fifty-one black currant cultivars of various genetic and ecogeographic origin were the material for the research. Cvs. ‘Nara’ (for early cultivars) and ‘Peterburzhenka’ (for mid-season and mid-late ones), both listed in the State Register of Selection Achievements for Northwest Russia, served as the references. The research was conducted by conventional methods. Statistical data processing was performed using Microsoft Excel and guidelines.Results and conclusions. As a result of the research, valuable genotypes with the best morphometric parameters and cultivars for commercial and amateur gardening were identified. Large fruit size and stability of this trait were observed in cvs. ‘Yubileinaya Kopanya’ (k-44189), ‘Selechenskaya 2’ (k-42637), ‘Litvinovskaya’ (k-45542), ‘Fortuna’ (k-44194), ‘Partizanka bryanskaya’ (k-45548), ‘Sofievskaya’ (k-43131), ‘Raduzhnaya’ (k-45549), ‘Karri’ (k-44172), and accession 2780-20-33 (k-49788). Cvs. ‘Kozatskaya’ (k-44187) and ‘Perezvon’ (k-45589) develop 8 berries per raceme. The best cultivars with optimal combinations of the studied traits, suitable for large-scale cultivation and amateur gardening in Northwest Russia, are ‘Andreevskaya’ (k-49787), ‘Kazkova’ (k-44196), Raduzhnaya’ (k-45549), ‘Sevchanka’ (k-45551), ‘Selechenskaya 2’ (k-42637), Sofievskaya’ (k-43131), ‘Tatran Slava’ (k-44182), ‘Karri’ (k-44172), and ‘Yubileinaya Kopanya’ (k-44189). Correlations between individual morphostructural yield components were identified.